The Amalgamation of Traditional and Contemporary Elements in Islamic Education (EDUKASIA, 2023)
This study uses Prophet Muhammad's integrated paradigm of Islamic intellectual heritage, which formed the epistemic foundation of the Medinah civilization. If Muslim scientists believed that expertise in one scientific field required proficiency in others or encyclopedic knowledge, polymath scientists have been replaced by highly specialized scientists who ignore these broader scientific regions. Contemporary Islamic scientific references, as a result, lack hybridity. Western knowledge typically trumps Islamic wisdom in scientific credibility. This study, thus, collected and analyzed data using qualitative methodologies and library resources. This study focuses on exploratory qualitative data from the perspectives of various scholars on the "Integration of Knowledge," aiming to reformulate an integration between traditional and contemporary knowledge that is adaptive in Indonesia’s education. Many epistemology studies have concentrated on Islamic literature and ignored Western knowledge. Unlike modern Eurocentrism, certain scientific integration studies value all information sources equally.